2013
DOI: 10.1136/tobaccocontrol-2012-050846
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tobacco policy in schools: upcoming preventive strategy or prevention myth? A review of 31 studies

Abstract: The evidence concerning the effectiveness of a school policy alone in preventing youth tobacco use is weak and inconclusive. Experimental studies or observational studies with longitudinal design are warranted, employing clear definitions of policy components and careful control for confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 47 publications
4
79
0
2
Order By: Relevance
“…There are many different school smoking policies and ways of implementing and enforcing these policies. A review by Galanti et al 8 suggested that some school smoking policies may be effective in the prevention of smoking among adolescents. For example, several studies suggested that strict bans on smoking in and around schools may decrease smoking prevalence 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different school smoking policies and ways of implementing and enforcing these policies. A review by Galanti et al 8 suggested that some school smoking policies may be effective in the prevention of smoking among adolescents. For example, several studies suggested that strict bans on smoking in and around schools may decrease smoking prevalence 9–13.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-smoking policy in Chinese schools is seemingly a well-structured system with education, monitoring, and enforcement processes. However, consistent with evaluations of the effectiveness of tobacco management in the West (Galanti et al, 2014), the policy does not appear to be effective.…”
Section: Discussionmentioning
confidence: 88%
“…The structural power between teachers and students at school is, therefore, likely to prompt students to challenge any health imperative from the school's authority (e.g., looking for the loopholes in tobacco management; Cothran & Ennis, 1997; S. Lewis & Russell, 2013). This finding also helps to explain why previous studies identified the positive associations between teachers' smoking and student smoking (Galanti et al, 2014;Paek, Hove, & Oh, 2013;Sinha, Gupta, Dobe, & Prasad, 2007).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations